Emerging risks in smart process industry cranes survey: SAF€RA research project SPRINCE - Spasojević-Brkić, Vesna K; Milazzo, Maria Francesca; Brkić, Aleksandar; Maneski, Tasko (Serbian Journal of Management, 2015)
Current accident theories show that the solution to avoid human error cannot be based on focusing only on the correction of operators’ behavior, but needs certain innovation that will help to keep an error away. Since, as evidenced by several incident surveys, cranes are the most dangerous equipment in industrial and construction sites and human error is the most frequent cause of accidents, in this frame the crane navigation system is an important and challenging component, with a great potential for safety improvement. However, as the emerging and rapid development of new technologies aims improving the working conditions and environment through solutions regarding existing well-known problems in occupational safety, their implementation also could lead to emerging hazards and risks that must be taken into account and managed. Based on these facts, SPRINCE (Smart PRocess INdustry CranEs) project aims implementing a real-time object detection solution, which deals with cranes’ tracking systems and incorporates visual feedback, developing and implementing an innovative tool for evaluation of organizational and human (operator-specific) factors. These factors will be included in the risk indicators of the implemented real-time object detection solution using case studies approach.